2023
DOI: 10.1002/hed.27515
|View full text |Cite
|
Sign up to set email alerts
|

It is time to improve the diagnostic workup of oropharyngeal cancer with circulating tumor HPV DNA: Systematic review and meta‐analysis

Francesca Paolini,
Flaminia Campo,
Oreste Iocca
et al.

Abstract: The possibility of detecting circulating tumor HPV DNA (ctHPVDNA) in plasma in patients with oropharyngeal cancer has been demonstrated in several reports. However, these data are from small cohorts and available tests for detection of ctHPVDNA are not fully validated. The aim is to evaluate sensitivity, specificity, and accuracy of ctHPVDNA by ddPCR to define its efficacy in the clinical setting for the diagnosis of HPV + OPSCC. A comprehensive search of three different databases: MEDLINE, Embase, and Cochran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…39 Finally, given interest in ctHPV DNA serving as a biomarker of early disease, the above analysis was repeated post hoc and compared between patients with localized (ie, stages 2 or 2) and advanced (ie, stages 3 or 4) tumors. [21][22][23][24][25] The generated SROC curves were plotted against one another on the same set of axes for qualitative comparison. Note that the study from Ahn et al 27 was excluded from these additional analyses due to its lack of available individuallevel patient data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…39 Finally, given interest in ctHPV DNA serving as a biomarker of early disease, the above analysis was repeated post hoc and compared between patients with localized (ie, stages 2 or 2) and advanced (ie, stages 3 or 4) tumors. [21][22][23][24][25] The generated SROC curves were plotted against one another on the same set of axes for qualitative comparison. Note that the study from Ahn et al 27 was excluded from these additional analyses due to its lack of available individuallevel patient data.…”
Section: Discussionmentioning
confidence: 99%
“…AUC values of 0.50, 0.70 to 0.80, 0.80 to 0.90, and above 0.90 were taken as the test conferring zero, acceptable, excellent, or outstanding predictive value, respectively, per literature recommendations . Finally, given interest in ctHPV DNA serving as a biomarker of early disease, the above analysis was repeated post hoc and compared between patients with localized (ie, stages 2 or 2) and advanced (ie, stages 3 or 4) tumors . The generated SROC curves were plotted against one another on the same set of axes for qualitative comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another dPCR assay (tumor tissue modified viral) has been validated in p16+ OPC in different cohorts [ 26 , 39 ] with pre-treatment sensitivity of 92.5% and negative predictive value (NPV) of 99.4% [ 25 ], but limited accuracy of MRD detection in the first 6 months post-CRT. A recent meta-analysis from several studies has shown a sensitivity of 91% for HPV DNA detection using different HPV genotypes including only plasma samples at diagnosis [ 40 ]. The sensitivity in our study at baseline was 100% for both HPV-seq and dPCR.…”
Section: Discussionmentioning
confidence: 99%